2015
DOI: 10.4103/0972-0707.164034
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of microshear bond strength of the caries-affected dentinal surface treated with conventional method and chemomechanical method (papain)

Abstract: Background:There is a growing interest in chemomechanical excavation (papain) in permanent molar teeth. There are several studies dealing with primary molar teeth.Aim:The aim of this study was to evaluate the influence of conventional method and Carie-care (chemomechanical method) on the microshear bond strength (μSBS) and the type of failure of an adhesive system to caries-affected dentin of permanent molar teeth.Materials and Methods:Twenty permanent molar teeth with carious lesions extending into the dentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The results were explained depending on the quality of adhesive bond at interfaces and failure pattern, as well. 25 In this study, groups (1&2) recorded the highest push-out bond strength among all groups. The main explanation was directed towards the minimal polymerization shrinkage of bulk-fill composite coupled by polymerization stress relieving properties.…”
Section: Discussionmentioning
confidence: 54%
“…The results were explained depending on the quality of adhesive bond at interfaces and failure pattern, as well. 25 In this study, groups (1&2) recorded the highest push-out bond strength among all groups. The main explanation was directed towards the minimal polymerization shrinkage of bulk-fill composite coupled by polymerization stress relieving properties.…”
Section: Discussionmentioning
confidence: 54%
“…The completeness of the caries removal was assessed by using the same criteria as for the first group. 3 …”
Section: Methodsmentioning
confidence: 99%
“…Jyothi et al studied the effects of Papacárie ® , a papain-based enzymatic gel, on the caries-affected dentin of permanent molars (Chittem et al, 2015). They reported that a regular and cracked surface could be observed on caries-affected dentin with a small smear layer and exposed dentinal tubules.…”
Section: Papain-based Enzymatic Gel Groupmentioning
confidence: 99%